2021
DOI: 10.1101/2021.01.05.20248973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between Stress and Child Verbal Abuse and Corporal Punishment during the COVID-19 Pandemic and Potential Effect Modification by Lockdown Measures

Abstract: BackgroundChild abuse appears to be on the increase during the COVID-19 pandemic, but the extent that lockdown measures modified the association between stress and abuses has not been systematically assessed.ObjectivesTo assess: 1) the association between caregiver’s stress and self-reported verbal abuse and corporal punishment of a child in the household, and; 2) modification of the stated association by experienced COVID-19 lockdown measures.Participants and settingsCaregivers residing in villages on lockdow… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Twelve articles examined two distinct types of stress during the pandemic, including parental and pandemic-related stress ( Bérubé et al, 2020 ; Brown et al, 2020 ; Calvano et al, 2021 ; Chung et al, 2020 ; Connell & Strambler, 2021 ; Freisthler et al, 2021 ; Jeharsae et al, 2021 ; Rodriguez et al, 2021 ; Spinelli et al, 2020 ; Taubman-Ben Ari et al, 2021 ; Wolf et al, 2021 ). Most cited was parental stress, which was implicated as a significant predictor for general CM, neglect, or punitive parenting across 5 of the 11 articles ( Bérubé et al, 2020 ; Chung et al, 2020 ; Spinelli et al, 2020 ; Taubman-Ben Ari et al, 2021 ; Wolf et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve articles examined two distinct types of stress during the pandemic, including parental and pandemic-related stress ( Bérubé et al, 2020 ; Brown et al, 2020 ; Calvano et al, 2021 ; Chung et al, 2020 ; Connell & Strambler, 2021 ; Freisthler et al, 2021 ; Jeharsae et al, 2021 ; Rodriguez et al, 2021 ; Spinelli et al, 2020 ; Taubman-Ben Ari et al, 2021 ; Wolf et al, 2021 ). Most cited was parental stress, which was implicated as a significant predictor for general CM, neglect, or punitive parenting across 5 of the 11 articles ( Bérubé et al, 2020 ; Chung et al, 2020 ; Spinelli et al, 2020 ; Taubman-Ben Ari et al, 2021 ; Wolf et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies also showed that abusive behavior increased relative to the number of children within the home (Jeharsae et al, 2021;Yamaoka et al, 2021). Caregiver educational attainment was positively associated with emotional violence but negatively associated with verbal abuse (Jeharsae et al, 2021) and witnessing family violence (Zhang et al, 2021). Risk for witnessing family violence, however, only increased relative to decreases in educational attainment among fathers (Zhang et al, 2021).…”
Section: Risk Factorsmentioning
confidence: 96%
See 1 more Smart Citation